Expanding Moral Understanding. Issue 3 (3rd July 2019) - Tierney, Hannah
ABSTRACT: In 'Forgiveness: An Ordered Pluralism, ' Fricker argues that the function of forgiveness is to liberate the forgiver from redundant blame-feeling. Blame is rendered redundant when it no longer serves its purpose, so to understand the function of forgiveness, we must understand the function of blame. For Fricker, the paradigmatic function of Communicative Blame is to align the moral understandings of wrongdoers and their victims, which is accomplished by wrongdoers coming to feel remorse. In this paper, I argue that Fricker should adopt a broader view of moral understanding and sever the connection between remorse and the alignment of moral understandings.